Pelatihan dan Pendampingan Digital Marketing bagi UMKM Jasa Laundry menuju UMKM Go Digital - Army Justitia; Indah Werdiningsih; Faried Effendy; Taufik Taufik (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
The COVID-19 pandemic has had a significant impact on Micro Small Medium Enterprises (MSMEs), especially laundry services in Plosokandang, Tulungagung Regency. Their primary customers, college students, no longer use their services because of online teaching and learning. The use of social media digital marketing is one solution to promote products and services. Unfortunately, many MSMEs lack this skill. This community service project focuses on training and assisting MSMEs in designing digital marketing content and posting them on their official social media. Canva software was chosen as a tool for content creation because it is simple and quick to use, with minimal design capabilities. Canva offers ready-made templates, so users only need to add their own personal touches. Then, the content is shared on the official social media accounts (Instagram or Facebook Pages). Participants’ and partners’ knowledge and skills improved after following the training. The average increase in participant knowledge of Canva material is 18.62 points, while social media material is 10.79 points. These training and mentoring activities have a positive impact on skills and knowledge related to using Canva and social media for digital marketing. Another effect of digital marketing on social media is an increase in revenue turnover, customer numbers, customer reach, and market sectors.